Modified interactive strut-and-tie model for shear strength prediction of RC corbels - Chetchotisak, Panatchai; Rulak, Parin; Teerawong, Jaruek (Engineering and Applied Science Research, 2019)
On the basis of the modified Kupfer and Gerstle’s biaxial failure criterion of concrete, a modified interactive strut-and-tie model (MISTM) to predict the nominal shear strength of RC corbels was derived and is proposed in this paper. The MISTM includes the interaction between the load-carrying capacity of a concrete strut and a tension tie, and the effects of horizontal force. The number of horizontal and vertical stirrups was considered. To validate and calibrate the MISTM, a dataset test results for 302 corbels was collected from the literature. Finally, the predictions obtained from the MISTM were also compared with those computed using the strut-and-tie models in accordance with the ACI 318 code and the state-of-the-art presented in the literature, and are found to be more accurate and reliable.